Teaching Basic English in Elementary School SDN 002 Kelurahan Lamaru - Nofan, Nofansyah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Basic English is essential to learn as it lays the foundation for future success. Teaching basic English from an early stage helps the younger generation expand their knowledge and prepare for higher career achievements. The teaching method emphasizes simplicity, focusing on three fundamental components of English grammar to ensure ease of understanding. The approach is designed to be efficient, with a focus on engaging students through interactive sessions. To boost motivation and maintain interest, quizzes with rewards are incorporated, making the learning process both enjoyable and effective. By combining simple yet structured teaching techniques with engaging activities, this method fosters enthusiasm and a solid grasp of basic English, equipping students with the necessary skills to thrive academically and professionally. The ultimate goal is to build a strong foundation for lifelong learning and better opportunities